Usability Testing On Game Interface Design Using Video-Based Behavior Analysis - Ahmad, Ibrahim; Abdullasim, Nazreen; Mohd Suaib, Norhaida (Science Publishing Corporation Inc, 2018)
The objective of this study is to quantitatively incorporate user observation into usability evaluation of game interface design.In this study,an experiment was conducted to monitor and record users' behavior using built in video-cam.The experiment was done after the user play “A Garuda” game.All the character movement controlled by user were captured and recorded for comparative analysis.There were about 20 people involved as a subject for this experiment.The data from video recordings were coded with Noldus Observer XT in order to find usage patterns and thus to gather quantitative data for analyzing the GUI effectiveness,efficiency and satisfaction.The result of user's interaction towards the design of game's GUI able to give additional information for the game designer to develop a better responsive game toward its usability.The effect of user's control and emotion that can be seen from user's face will give the information needed to be considered in game development. Previous studies mostly focusing on evaluating the usability with performance measures by only looking at task results.Thus,at the end of this study,a method is proposed by incorporating user observation into usability evaluation of game design interfaces.